The CC genotype of the delta-sarcoglycan gene polymorphism rs13170573 is associated with obstructive sleep apnea in the Chinese population. - Rensong Ye; Wenlan Yang; Yiming Yuan; Xingqi Deng (PLoS ONE, 2014)
Obstructive sleep apnea (OSA) is a highly heterogeneous sleep disorder, and increasing evidence suggests that genetic factors play a role in the etiology of OSA. Airway muscle dysfunction might promote pharyngeal collapsibility, mutations or single nucleotide polymorphisms (SNPs) in the delta-sarcoglycan (SCGD) gene associated with muscle dysfunction. To evaluate if SCGD gene SNPs are associated with OSA, 101 individuals without OSA and 97 OSA patients were recruited randomly. The genotype distributions of SNPs (rs157350, rs7715464, rs32076, rs13170573 and rs1835919) in case and control populations were evaluated. The GG, GC and CC genotypes of rs13170573 in control and OSA groups were 51.5% and 37.1%, 36.6% and 35.1%, and 11.9% and 27.8%, respectively. Significantly fewer OSA patients possessed the GG genotype and significantly more possessed the CC genotype compared with controls. Further multivariate logistic regression analysis showed that the CC genotype was an independent risk factor for OSA, with an odds ratio (OR) of 2.17 (95% confidence interval [CI]: 1.19-6.01). Other factors, such as age ≥ 50 years, male gender, body mass index (BMI) ≥ 25 kg/m(2), low-density lipoprotein cholesterol (LDL-C) level ≥ 3.33 mg/dL, smoking and hypertension, were also independent risk factors for OSA in our multivariate logistic regression model.